Effect of brisk walking intervention in occupational populations with normal high blood pressure: an isotemporal substitution model-based analysis - Kaiming GUO; Yifan ZHAO; Pingping ZHAO; Fang LIU; Xi XU; Chao ZHANG; Maigeng ZHOU; Wei JIANG (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo examine the effect of brisk walking intervention in occupational populations with normal high blood pressure, and to provide quantified evidence for health improvement of occupational population with normal high blood pressure. MethodsThe information on demographics, physical examination and walking of 4 855 workers with normal high blood pressure were extracted from a brisk walking incentive intervention program for occupation populations conducted during 2016 in China. The substitution effects of low intensity physical activity (LPA), moderate intensity physical activity (MPA) and high intensity physical activity (HPA) instead of sedentary behavior (SB) on health outcomes were analyzed with isochronal substitution model. Results The results of isochronous substitution model analysis showed that the body mass index (BMI), body fat rate (BFP) and visceral fat index (VAI) of occupational people with normal high blood pressure decreased by 0.102 (β = - 0.102), 0.150% (β = - 0.150) and 0.071 (β = - 0.071), respectively when the SB was replaced by MPA time of 30 min/d during the same period. The results of subgroup analysis showed that MPA time of 30 min/d instead of SB during the same period could decrease BMI by an additional 0.120 (β = - 0.120) in male occupational population with normal high blood pressure, and an additional 0.287% (β = - 0.287) and 0.119 (β = - 0.119) in BFP and VAI in female occupational group with normal high blood pressure, respectively. BMI, BFP and VAI decreased by 0.127 (β = - 0.127), 0.192% (β = - 0.192), and 0.098 (β = - 0.098) in normal high blood pressure occupational group aged 49 years old; while BMI and VAI decreased by 0.160 (β = 0.160) and 0.080 (β = - 0.080) in overweight and obese occupational group. BMI, BFP and VAI decreased by an additional 0.206 (β = - 0.206), 0.216% (β = - 0.216) and 0.127 (β = - 0.127), respectively, and BMI and BFP decreased by an additional 0.063 (β = - 0.063) and 0.143% (β = - 0.143) in normal high blood pressure occupation group with normal BFP. The BMI could be decreased by 0.189 (β = - 0.189) in the normal high blood pressure occupational group with BFP-indicated obesity, while the BMI, BFP and VAI could be decreased by 0.144 (β = 0.144), 0.200% (β = - 0.200) and 0.104 (β = - 0.104) in the normal high blood pressure occupational group with VAI-indicated obesity. A 30 min/d HPA time instead of SB during the same period resulted in an additional decrease of 0.641% (β = - 0.641) and 0.295 (β = - 0.295) in BFP and VAI in men with normal high blood pressure, and an additional 1.020% (β = - 1.020) and 0.520 (β = - 0.520) in BFP and VAI in those ≥ 50 years old; BFP could be decreased by an additional 0.748% (β = - 0.748) in normal high blood pressure occupational population with BFP-indicated obesity. Conclusion A 30 min/d MPA time instead of SB during the same period can improve the BMI, BFP and VAI at different degrees in the occupational populations with normal high blood pressure; however there may be no isochronous substitution for health improvement effect of LPA and HPA instead of SB in the whole population; the moderate intensity walking exercise of 100 - 130 steps/min can be promoted in this population.